Students' mindsets on research integrity-a cross-cultural comparison - Milena Valeva; Petya Dankova; Julia Priess-Buchheit (Canadian Science Publishing, 2022)
Research integrity (RI) has been a focus of society in recent years as a means to create and to keep trust in science. Higher education institutions (HEIs) play a key role in promoting a culture of RI and responsible conduct of research (RCR). The understanding and practice of RI can vary across cultures. This article aims to outline initial insights into university students' RI mindsets based on five RI facets: understanding, importance, value-action gap, enforcement approaches, and training. A qualitative exploratory cross-cultural study was conducted with participants from Germany and Bulgaria via semi-structured guided group interviews. An explicit transcultural agreement regarding the significance of RI was categorically indicated. Intercultural differences between the two European countries were revealed and discussed in reference to understanding RI, the value-action gap, enforcement approaches, and training preferences.